Man up and take it: Gender bias in moral typecasting - Reynolds, Tania; Howard, Chuck; Sjåstad, Hallgeir; Zhu, Luke; Okimoto, Tyler G.; Baumeister, Roy F.; Aquino, Karl; Kim, JongHan (Organizational behavior and human decision processes, 2020)
•We predicted and supported a gender bias in moral typecasting.•Victims were assumed to be female and perpetrators were assumed to be male.•A female (vs male) employee complaining of harassment was seen as more of a victim.•People desired harsher punishments for male than female perpetrators.•Managers who fired female (vs male) employees were perceived as less moral. Informed by moral typecasting theory, we predicted a gender bias in harm evaluation, such that women are more easily categorized as victims and men as perpetrators. Study 1 participants assumed a harmed target was female (versus male), but especially when labeled ‘victim’. Study 2 participants perceived animated shapes perpetuating harm as male and victimized shapes as female. Study 3 participants assumed a female employee claiming harassment was more of a victim than a male employee making identical claims. Female victims were expected to experience more pain from an ambiguous joke and male perpetrators were prescribed harsher punishments (Study 4). Managers were perceived as less moral when firing female (versus male) employees (Study 5). The possibility of gender discrimination intensified the cognitive link between women and victimhood (Study 6). Across six studies in four countries (N = 3,137), harm evaluations were systematically swayed by targets’ gender, suggesting a gender bias in moral typecasting.